The globotics upheaval : globalization, robotics, and the future of work - Baldwin, Richard E. (New York, NY : Oxford University Press, 2019)
" At the root of inequality, unemployment, and populism are radical changes in the world economy. Digital technology is allowing talented foreigners to telecommute into our workplaces and compete for service and professional jobs. Instant machine translation is melting language barriers, so the ranks of these "tele-migrants" will soon include almost every educated person in the world. Computing power is dissolving humans' monopoly on thinking, enabling AI-trained computers to compete for many of the same white-collar jobs. Richard Baldwin, one of the world's leading globalization experts, argues that the inhuman speed of this combination of globalization and robotics - "globotics" - threatens to overwhelm our capacity to adapt. Globotics will disrupt the lives of millions of white-collar workers much faster than automation, industrialization, and globalization disrupted the lives of factory workers in previous centuries. The result will be a backlash. Professional, white-collar, and service workers will agitate for a slowing of the unprecedented pace of disruption, as factory workers have done in years past. Baldwin argues that the globotics upheaval will be countered in the short run by "shelter-ism" - government policies that shelter some service jobs from tele-migrants and thinking computers. In the long run, people will work in more human jobs - activities that require real people to use the uniquely human ability of independent thought - and this will strengthen bonds in local communities. Offering effective strategies such as focusing on the social value of work, The Globotics Upheaval will help employers and institutions prepare for the oncoming wave of an advanced robotic workforce. "--
"Digital technology will bring globalisation and robotics (globotics) to previously shielded professional and service sectors. Jobs will be displaced at the eruptive pace of digital technology while they will be replaced at a normal historical pace. The mismatch will produce a backlash - the globotics upheaval"--
Machine generated contents note: -- Introduction -- PART I: HOW WE GOT HERE -- Chapter 1: The Great Transformation: Globalization, Automation, and Technology -- Chapter 2: The Great Upheaval: Backlash and Reform -- Chapter 3: Today's Globalization, Automation, and Backlash -- PART II: WHERE WE ARE GOING -- Chapter 4: Technology driving the Globotics Revolution -- Chapter 5: The Next Great Transformation -- Chapter 6: The Next Great Upheaval -- PART III: HOW TO PREPARE -- Chapter 7: How to Prepare -- Chapter 8: Profiting from the Peril -- Chapter 9: Job-centric Capitalism won't Work without Jobs.
Includes index.
Keywords: Automation -- Economic aspects; Employees -- Effect of technological innovations on; Globalization -- Economic aspects; Robotics -- Economic aspects; BUSINESS & ECONOMICS / Development / General; BUSINESS & ECONOMICS / Office Automation; TECHNOLOGY & ENGINEERING / Robotics